Determination of Multiple-target Equivalent Static Wind Load of Large-span Roof Structures based on Clustering Analysis Techniques - Huang, Ming-Hui; Fu, Chung-Lin; Hsu, Yu-Wen; Lo, Yuan-Lung (International Journal of Architectural Engineering Technology, 2023)
Spatial structures in modern society exhibit a city’s distinguishing features and show its strength in building technology. Large-span roof structures are mostly seen among spatial structures for various activities. Large-span roof structures are usually sensitive to wind loads due to their lightness in materials and curved geometric appearance. However, spatial structures are generally designed with many structural members, making it challenging to determine adequate load distributions for structural safety analysis. This paper intends to introduce the concept of the multiple-target equivalent static wind loads and to demonstrate how to reduce the heavy computational burden when the structural designer needs to consider multiple loading effects of the target structure. The wind tunnel test of an elliptical-shaped stadium structure with a flat roof is first conducted to show the fundamental aerodynamic characteristics. The methodologies of the background-component wind force based on the load-response-correlation (LRC) method and the resonant-component wind force based on the inertial force method are then introduced for the specification of single-target equivalent static wind loads. Finally, the clustering analysis technique is adopted to explain the concept of the multiple-target equal static wind loads. A decay index is proposed to indicate how the clustering technique improves the specification of equivalent static wind loads.